Kepribadian Tokoh dalam Kumpulan Naskah Drama Perjuangan Laskar Tujuh Belas Karya Ari Sulistyo - Nuraini Nuraini; Noni Andriyani (UIR Press, 2022)
This research is motivated by several things, namely (1) Seeing the many aspects of literary psychology in the collection of drama scripts of the struggle of the Seventeen Laskar by Ari Sulistyo. (2) Research on drama scripts using literary psychology theory is rarely done, because most people are more familiar with a drama through performances than reading the drama script itself. Personality psychology is the study of human personality with the object of research on factors that influence human behavior. In personality psychology studied the relationship between memory or observation with development, the relationship between observation and adjustment to the individual. According to Freud,